2015
DOI: 10.1589/jpts.27.3369
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of walker-aided walking by the healthy elderly with a walker pocket of different weights attached at different locations

Abstract: [Purpose] This study aims to provide information on safe walker-aided walking by analyzing elderly subjects’ walking with a walker pocket of different weights attached at different locations. [Subjects and Methods] Twenty elderly right-handed males participated in the study, and a walking analyzer was used to examine their walking with a pocket attached to the left, center, and right side of the walker. The weight of the pocket was set at three levels relative to the average weight of the subject group: 0% (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Although we did not observe a statistically significant difference in our study, we found that gait variables were most efficient when the WAV was loaded with a weight of 5% compared to when no weight was added (0%). This shows that an appropriate weight in the WAV has a positive effect on gait by reducing the limitations accompanying physical activity (Shin et al, 2015). Specifically, using an appropriate weight positively lowers the center of mass of the WAV, thereby enhancing trunk stability, reducing tremor of the WAV during movement, and facilitating efficient, stable gait.…”
Section: ⅳ Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although we did not observe a statistically significant difference in our study, we found that gait variables were most efficient when the WAV was loaded with a weight of 5% compared to when no weight was added (0%). This shows that an appropriate weight in the WAV has a positive effect on gait by reducing the limitations accompanying physical activity (Shin et al, 2015). Specifically, using an appropriate weight positively lowers the center of mass of the WAV, thereby enhancing trunk stability, reducing tremor of the WAV during movement, and facilitating efficient, stable gait.…”
Section: ⅳ Discussionmentioning
confidence: 92%
“…The excessive force required when carrying too much weight increases physical burden and center of mass and trunk movements, which in turn elevates the risk of gait impairment due to reduced ability to maintain balance. Thus, through the contribution of the WAV instability, the risk of overturning increases, which presents considerable danger to elderly individuals during walking (Shin et al, 2015). For this reason, the carrying weight should be considered when using WAVs (Park and Cho, 2008).…”
Section: ⅰ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few researchers have attempted to assess gait functionality while using a walker, from the perspective of biomechanics 6,7) . Fast et al 8) evaluated the pattern and magnitude of forces transmitted through the frames of walkers during ambulation.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the damage level, it is possible to recommend the use of walking sticks, walkers, wheel walkers or, in extreme cases, wheelchairs. Walkers are used to help balance and totally or partially reduce the weight support of the lower limbs (12)(13) . In addition to common walkers, locomotion trainings based on the partial weight support provide positive results in the static and dynamic balance and help performing the functional gait (12) .…”
Section: Introductionmentioning
confidence: 99%